A rare case of tumoral scleromyxedema - Ali Sadeghinia; Mohammad Al Salman; Jafar Taghizadeh Fazli; Pedram Normohammadpour; Amir Hooshang Ehsani; Seyed Naser Emadi (Wolters Kluwer Medknow Publications, 2020)
Scleromyxedema is an uncommon disease, affecting the skin mainly and other internal organs sometimes, characterized by fibroblasts proliferation, fibrosis, and mucous deposition in the absence of thyroid disorder. It is associated with monoclonal gammopathy in most cases. We are reporting a case with a rare presentation of tumoral scleromyxedema in the neck, with a mass mimicking other tumoral lesions, highlighting the importance of diagnosis and histopathologic correlation.